Japan on the upswing : why the bubble burst and Japan's economic renewal - Iwamoto, Yoshiyuki (Algora, 2006)
Japan's effervescent economy, charging ahead in the late 1980s under the stimulation of a two and a half percent prime rate, shook American confidence ... until the bubble burst in 1989, leaving banks saddled with over $200 billion in bad loans. Iwamoto shows how and why the lenders racked up all this uncollectible debt, who took advantage of whom and how actions by business and government officials contributed to the crisis. Along the way, his illustrative examples share some of the flavor of business life in Japan including the academic cliques and mobster clans, the after-hours camaraderie and the legendary "entertainment" that was used to evade inspections by the Ministry of Finance. The author then describes Prime Minister Koizumi's initiatives that halved the bad loans by March 2005 and inspired foreign investors to bring back their cash. With strong exports, increasing capital investment and decreasing unemployment, Japan is truly on the upswing. Koizumi's party reaped the benefit with a landslide victory in the September 2005 general election, and he continues to push for further restructuring. The author goes on to identify and describe the 20 most successful companies in Japan this year, and gives clues as to what makes them thrive. Many aspects of Japan's economy are highlighted in tables and statistics, from "Differences in Pay Scale by Type of Industry" to "Results at Seven Mega Banking Groups and Forecast for March 31, 2006," plus balance sheets of companies like Toyota, Shiseido and McDonald's Japan